Pengembangan Bahan Ajar Persamaan Diferensial Berbasis Model Brown Di Program Studi Pendidikan Matematika Fakultas Keguruan Dan IlmuPendidikan Universitas Kristen Indonesia Tahun 2017/2018 - Jitu Halomoan Lumbantoruan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
Differential equations are mathematical equations for functions of one or more variables, which relate the value of the function itself and its derivatives in different order. As a prospective teacher, students are required to master the cognitive domain of differential equations. Based on the observations made where tested the initial knowledge of students in the course of differential equations and found 80% of students are not biased deserve to be said to pass. Therefore, this research is aimed at 1. Developing instructional of differential equations based on brown model and cooperative learning model as a tool in learning process; 2. Testing the effectiveness of teaching materials of developed differential equations; 3.Test whether there is a good improvement in learning outcomes in the teaching and learning process using the teaching aid tool. The method used in this research is development research. From this result Researchers believe that in the course of teaching materials is very effective tool process of course in the classroom. Keywords: Course Tools, Differential Equations.